Nilai Ekonomi Islam: Degradasi Lingkungan, Kemiskinan, Modal Manusia, terhadap Pertumbuhan Ekonomi Indonesia. Hipotesa Kuznetz - Damayanti, Alfina Damayanti; Iryana, Wahyu; Rahman, Taufiqur (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2025)
This study analyzes the influence of environmental degradation, poverty, and human capital on Indonesia’s economic growth from 2001 to 2024 using the Vector Error Correction Model (VECM). The results indicate a long-term equilibrium among variables, where environmental degradation and poverty positively and significantly affect economic growth, while human capital has a negative and significant effect. These findings suggest that Indonesia’s growth still relies on natural resource exploitation and faces challenges in optimizing human capital quality. In the short run, no significant relationships are found, implying that impacts occur cumulatively over time. The results support the Environmental Kuznets Curve (EKC) hypothesis, showing that early-stage economic growth is often accompanied by inequality and environmental decline. From an Islamic economic perspective, sustainable and just development should be pursued in line with maqāṣid al-sharī‘ah, emphasizing balance, justice, and responsible resource management.